2009
DOI: 10.1075/cilt.306.05che
|View full text |Cite
|
Sign up to set email alerts
|

The phonetics of sentence-initial topic and focus in adult and child Dutch

Abstract: This study investigates whether adults and children use phonetic means to distinguish sentence-initial topic and focus marked with the same accent type (H*L) in Dutch declaratives. It was found that in adults’ speech, the falling accent starts to fall earlier and has a larger F0 excursion and lower F0 minimum in focus than in topic. Further, the low F0 is maintained longer in focus. Moreover, the accented syllable and word are longer in focus than in topic. In contrast, children do not yet use any of the phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 0 publications
6
49
0
Order By: Relevance
“…With respect to prosody, the current results mirror existing studies in showing that 4- to 5-year-olds use prosody to mark information structure, but are not yet employing it in a completely adult-like manner (e.g., Wells et al, 2004; Chen, 2007, 2009, 2011). More specifically, our participants deviated from adult speech through incomplete application of prosodic focus marking strategies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…With respect to prosody, the current results mirror existing studies in showing that 4- to 5-year-olds use prosody to mark information structure, but are not yet employing it in a completely adult-like manner (e.g., Wells et al, 2004; Chen, 2007, 2009, 2011). More specifically, our participants deviated from adult speech through incomplete application of prosodic focus marking strategies.…”
Section: Discussionsupporting
confidence: 82%
“…However, in children's speech focus was less clearly associated with falling accents (see de Ruiter, 2014, for somewhat different results regarding givenness). Chen (2011) only found a completely adult-like use of accent type in 7- to 8-year-olds, but even at this age, focus marking in terms of duration and alignment of f 0 turning points was not yet completely adult-like (Chen, 2009). Wells et al (2004) have reported that children's ability to mark focus condition prosodically and especially their ability to correctly identify information structure in language input continues to improve between age five and age thirteen.…”
Section: Introductionmentioning
confidence: 99%
“…A semi-spontaneous approach was adopted from [5] to elicit focus marking in SVO sentences. There were five different focus conditions: narrow focus on the subject NP in sentenceinitial position: NF-i, example (1) (1) to (5), where focused constituents appear in square brackets.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…It has also been shown that the use of pitch or duration is not related to the tonal aspects of a language [6]. For instance, both tone (e.g., Mandarin [4,7], Vietnamese [8]) and non-tone languages (e.g., English [3], Dutch [5], German [9]) use pitch range and duration for focusmarking purposes, whereas other languages only use duration to mark focus, such as Cantonese [10], Yi [11], Tsat [12], Bai [13] and Deang [11]. In addition, there are tone languages that do not use prosodic cues (pitch or duration) at all to mark focus, e.g., Yucatec Maya [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In languages that use prosody for marking focus, the prosodic cues involved differ from one language to another. For instance, some languages (such as English [1], Dutch [2,3] and Mandarin [4,5]) not only expand the pitch range and lengthen the duration of the focal constituent, but also compress the pitch range and intensity of the post-focal constituent. However, other languages only exploit duration for the same purpose (such as Cantonese [6], Tsat [7] and Bai [8]).…”
Section: Introductionmentioning
confidence: 99%